The effects of 11+ dance on physiological parameters in adolescent ballet dancers: A randomized controlled equivalence trial - Kolokythas, N.; Metsios, G. S.; Galloway, S. M.; Allen, N.; Wyon, M. A. (Journal of Dance Medicine & Science, 2025)
Introduction: The use of neuromuscular interventions in sports induce meaningful motor performance in strength, sprint and power. The aim of this study was to investigate the effectiveness of the "11+ Dance" exercise program versus normal training (control) on possible adaptations in power, lower-body strength, and inter-limb asymmetry in adolescent ballet dancers.